Stagnation Criminal Law Enforcement Post Determination Change Omnibus Law Act - Andini, Orin Gusta; Pradana , Syafa'at Anugrah; Gusreyna, Lisa Aprillia; Eriansyah, Surya (DIKTUM: Jurnal Syariah dan Hukum, 2023)
The purpose of this study is to investigate the application of criminal law following the determination of changes to the omnibus law and the influence such changes have on legal certainty. The study method that is being utilized is known as normative legal research, and it involves approaching the topic from legislative perspectives, conceptual perspectives, and case perspectives. According to the findings of the study, the process of criminal law enforcement has slowed down significantly in several areas where the omnibus law has made changes. This is true not only for cases that have recently taken place, but also for cases that are still in the stages of investigation and prosecution, which has led to a number of criminal cases not being resolved in court. This is due to the fact that the Omnibus Law has removed several criminal provisions from the previous law, including changing criminal sanctions to administrative sanctions. Furthermore, the Constitutional Court's decision on the Omnibus Law has never provided clarity on its application, which has caused criminal law enforcement to become stagnant. The word "stagnation" is synonymous with "bottleneck," "congestion," and "deadlock." After the stipulation of revisions to the Omnibus Law, there was a lull in the activity of criminal law enforcement, which resulted in the absence of legal certainty.